(x cosA + y sinA)^2 + (x sinA - y cosA)^2 = x^2+ y^2
LHS
(x cosA + y sinA)² + (x sinA - y cosA)²
expanding using the formula (a+b)²=a²+2ab+b² and (a-b)²=a²-2ab+b²
(x cosA)²+2(xcosA)(ysinA) + (y sinA )² + (x sinA)² - 2(x sinA)(y cosA) +(y cosA)²
x² cos²A + 2(xcosA)(ysinA) + (y² sin²A ) + (x² sin²A) - 2(x sinA)(y cosA) +(y² cos²A)
x²(cos²A+sin²A) +y²(sin²A+cos²A) +2(xcosA)(ysinA)- 2(x sinA)(y cosA)
We apply rule here sin²A+cos²A=1 and
cancelling 2(xcosA)(ysinA)- 2(x sinA)(y cosA)
we get x²+y²
RHS : x²+y²
LHS=RHS
HENCE PROVED